Analysis of The Marketing Mix “Our” Rice Sales On Purchase Satisfaction at The Makassar Branch Of Bulog - Fatmawati Fatmawati; Muhammad Darwis; Aris Baharuddin (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine how the Marketing Mix Analysis of Rice Sales